ZONASI TINGKAT KERAWANAN BANJIR DENGAN SISTEM INFORMASI GEOGRAFIS PADA DAS SEKITAR PERUMAHAN BUMI KARTIKA DRAMAGA, BOGOR - Syaiful, Syaiful; Aminda, Renea Shinta; Aminda, Annisa; Sandy, Awang Muhamad (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIKA Bogor, 2025)
The phenomenon of flooding often strikes a watershed area that is unable to accommodate the rainwater that falls because the amount of rainwater exceeds the capacity of the watershed itself. based on the geographic information system, it can be determined which areas require priority watershed management. The method used in this study is to map the level of flood vulnerability with a scoring and weighting technique. The results show that the areas classified as very flood-prone are mostly in the downstream area of the watershed which is located in the lowlands with most of the land use being open and built up, namely around the Bumi Kartika Dramaga housing complex, Ciherang, Bogor City.